Incidence and risk factors of pain following breast cancer surgery: a retrospective national inpatient sample database study - Shanlian Suo; Rui Liu; Xuegao Yu; Jian Wang; Min Wang; Yan Zhang; Yuqian Liu (BMC, 2024)
Abstract Background Postoperative pain (PP) is a dynamic process that reflects the complex interplay between symptoms, treatment, and patient experiences, and its intensity is reportedly primarily related to the severity of surgical trauma. However, no large-scale national database-based study has hitherto been conducted to assess the occurrence and features related to PP following breast cancer (BC) surgery. Methods In this retrospective analysis, we screened BC surgery cases between 2015 and 2019 within the National Inpatient Sample (NIS) Database, utilizing the International Classification of Diseases (ICD) 10th edition clinical modification codes. The researchers identified patients who developed PP and compared them to those who did not. Factors associated with PP were then screened: patient demographics (age and race), hospital characteristics (type of insurance, bed size, teaching status, type of admission, location, and hospital area), length of stay (LOS), total cost during hospitalization, inpatient mortality, comorbidities, and perioperative complications. Data were analyzed using descriptive statistics. Multivariate logistic regression analysis was used to determine the independent risk factors for postoperative pain in BC surgery. Results 39,870 BC surgery cases were identified over a five-year period from 2015 to 2019. The overall occurrence of PP following breast cancer surgery was 6.15% (2,387 cases), with a slight upward trend every year. Significant racial disparities were observed, Whites associated with a higher incidence of PP (P < 0.001). In addition, the incidence of elective admission was 11.96% lower (67.491% vs. 79.451%) than that of patients without PP following breast cancer surgery (P < 0.001). Besides, PP was related to prolonged hospitalization duration (3 vs. 2 days; P < 0.001), and higher total cost ($68,283 vs. $60,036; P < 0.001). Multivariate logistic regression identified breast cancer surgery-independent risk factors for PP, including younger age, non-elective hospital admission, rural hospitals, depression, drug abuse, metastatic cancer, psychoses, weight loss, and chronic pulmonary disease. In addition, postoperative pain for BC was associated with urinary retention, gastrointestinal complications, continuous invasive ventilation, deep vein thrombosis, urinary tract infection, blood transfusion, arrhythmia, and chest pain. Conclusion Despite the low incidence of postoperative pain in BC surgery cases, it is essential to investigate factors predisposing to PP to allow optimal care management and improve the outcomes of this patient population.